Proline modulates the Trypanosoma cruzi resistance to reactive oxygen species and drugs through a novel D, L-proline transporter - Martínez Sayé, Melisa Soledad (2014)
Trypanosoma cruzi, the etiological agent of Chagas' disease, has a metabolism largely based on the consumption of glucose and proline. This amino acid is essential for host cells infection and intracellular differentiation. In this work we identified a proline transporter (TcAAAP069) by yeasts complementation assays and overexpression in Trypanosoma cruzi epimastigotes. TcAAAP069 is mono-specific for proline but presents an unusual feature; the lack of stereospecificity, because it is competitively inhibited by the D- enantiomer. Parasites overexpressing TcAAAP069 have an increased intracellular proline concentration, 2.6-fold higher than controls, as a consequence of a higher proline transport rate. Furthermore, augmented proline concentration correlates with an improved resistance to trypanocidal drugs and also to reactive oxygen species including hydrogen peroxide and nitric oxide, emulating natural physiological situations. The IC50s for nifurtimox, benznidazole, H2O2 and NO. were 125%, 68%, 44% and 112% higher than controls, respectively. Finally, proline metabolism generates a higher concentration (48%) of ATP in TcAAAP069 parasites. Since proline participates on essential energy pathways, stress and drug resistance responses, these results provide a novel target for the development of new drugs for the treatments for Chagas' disease.